Vulnerability and Resilience in Patients with Chronic Pain in Occupational Healthcare: A Pilot Study with a Patient-Centered Approach. (2nd December 2018) - Peilot, Birgitta; Andréll, Paulin; Gottfries, Johan; Sundler, Annelie J.; Mannheimer, Clas
Abstract : Objectives . The aim of this pilot study was to describe vulnerability and resilience and possible subgroups in patients with chronic work related musculoskeletal pain in occupational healthcare. A second aim was to evaluate a patient-centered approach. Methods . This study was based on consecutive patients with chronic pain, seen by the same physician and sick-listed full or part time three months or longer. They were included during a period of three months. Patient reported outcome measures (PROM) were administered at baseline and at follow-up after 8 months. A patient-centered approach was applied where the patient's whole situation was taken into account. Results . A dominance of an insecure dismissing attachment pattern and a subnormal sense of coherence (SOC) was reported both at baseline and at follow-up. The patients (n=38) reported significant improvement of pain severity ( p =0.01), pain interference ( p =0.001), life control ( p =0.01), affective distress ( p =0.02), and dysfunction ( p =0.001) on the multidimensional pain inventory (MPI) and fewer patients were sick-listed full time at follow-up (13 patients versus 21). By means of multivariate data analyses this change in MPI was confirmed and was also correlated with a significant increase in health related quality of life (HRQoL). Moreover subgroups with different outcome at follow-up were identified according to attachment pattern and subgroups on MPI. Conclusion . A patient-centered approach may be of value for patients with chronic pain in occupational healthcare, improving pain and dysfunction. Patients with chronic pain are a heterogeneous group where outcome of treatment might be influenced by individual resilience and/or vulnerability.